VD_FINDINFO HC / 2016 / 663 vom 8. Juli 2016 - VD Tribunal cantonal (2016)
MOTIF DU RECOURS, APPRÉCIATION DES PREUVES, CHOSE JUGÉE | 267 al. 1 CO, 271 al. 1 CO, 272 CO, 97 CO, 311 al. 1 CPC (CH), 317 al. 1 CPC (CH)